Gender differences in preservice mathematics and science teachers’ professional identities - Ladapa Ladachart; Wittaya Pulsawad; Anusorn Tong-on; Luecha Ladachart (LUMAT)
The traditional marginalization of women in science, technology, engineering, and mathematics (STEM) may prevent female preservice teachers from seeing themselves as STEM teachers. However, gender differences in this issue remain underexplored. This study aims to examine whether and in what respects female preservice teachers differ in terms of their professional identities from their male counterparts. Participants include those majoring in mathematics (42), general science (44), and advanced science (47). The instruments include three versions of a Likert-type questionnaire measuring professional identities as general, disciplinary, and STEM teachers. Data were analyzed using Mann-Whitney U tests focusing on three components of professional identity (i.e., motivation, self-efficacy, and self-image). The results reveal that gender differences seldom occur in all respects, except when those majoring in advanced science self-identify as STEM teachers. Finally, this study provides implications regarding teacher education for STEM.